Correlation of Professional Nursing Practice Model on Motivation and Organizational Culture for Students at Blambangan Hospital - Ulumi, Bahrul; Hanik Endang Nihayati; Ilya Krisnana (Universitas Nahdlatul Ulama Surabaya, 2024)
The system of MPKP is a framework that explains four elements: standards, process of nursing, education of nursing, and the system of MPKP. Hospital organizations aim to provide good quality service to the patients.Patient satisfaction is directly influenced by the quality of services provided, especially matters related to the facilities and process of resource services in the hospital. This study aimed to determine the relationship between the Professional Nursing Practice Model (MPKP) and motivation and culture for nursing education students at Blambangan Hospital Banyuwangi. The type of research used was quantitative with a cross-sectional design. Hypothesis test was carried out using product moment correlation and multiple correlation analysis tests. This study’s results stated a significant correlation between the types of Professional Nursing Practice Model (MPKP) with a value of 0.842 ≥ 0.334. In addition, there was a significant correlation between motivations on the motivation of nursing education students with a value of 0.842 ≥ 0.334, and there was a significant correlation between the Professional Nursing Practice Model (MPKP) on organizational culture for nursing education students with a value of 0.862 ≥ 0.334. The results showed that there is a significant correlation between the type of Professional Nursing Practice Model (MPKP) on motivation and organizational culture for nursing education students at Blambangan Hospital. Keywords: Professional Nursing Practice Model (MPKP), motivation, organizational culture